AKTIVITAS ANTIBAKTERI FRAKSI N-HEKSAN, ETIL ASETAT DAN AIR EKSTRAK ETANOL DAUN SUKUN (ARTOCARPUS ALTILIS) TERHADAP PROPIONIBACTERIUM ACNES - Hadijah, Sitti; Jangga; Mewar, Djulfikri; Rahmadani, Hijrah (Jurnal Biogenerasi, 2025)
The purpose of this study was to determine the antibacterial activity of n-hexane, ethyl acetate and water fractions of breadfruit leaves (Artocarpus altilis) against Propionibacterium acnes. This research method is a laboratory experimental method using a maceration extraction process with 96% ethanol solvent, then the results of the thick extract were diffracted using n-hexane, ethyl acetate and water solvents made with concentrations of 10%, 15% and 20% for each fraction. Furthermore, phytochemical screening and antibacterial activity tests were carried out against Propionibacterium acnes in each fraction. The inhibition zone against Propionibacterium acnes bacteria in the water fraction with a concentration of 10% was 12.47 mm, 15% was 12.88 mm and 20% was 13.37 mm. The inhibition zone of the ethyl acetate fraction with a concentration of 10% was 12.22 mm, a concentration of 15% was 12.62 mm and a concentration of 20% was 13.27. The inhibition zone in the n-hexane fraction with a concentration of 10% was 12.42 mm, 15% was 12.68 mm and 20% was 13.25 mm. It was concluded that for the n-hexane fraction, ethyl acetate and breadfruit leaf water (Artocarpus altilis) have antibacterial activity against Propionibacterium acnes.